2014
DOI: 10.2147/vhrm.s60312
|View full text |Cite
|
Sign up to set email alerts
|

How are patients with type 2 diabetes and renal disease monitored and managed? Insights from the observational OREDIA study

Abstract: Background and aimChronic kidney disease (CKD) is frequent in type 2 diabetes mellitus (T2DM), and therapeutic management of diabetes is more challenging in patients with renal impairment (RI). The place of metformin is of particular interest since most scientific societies now recommend using half the dosage in moderate RI and abstaining from use in severe RI, while the classic contraindication with RI has not been removed from the label. This study aimed to assess the therapeutic management, in particular th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 54 publications
2
17
1
Order By: Relevance
“…This was a sub-analysis of data in patients ≥75 years old from the previously published OREDIA study. 13 OREDIA was a multicenter, observational, cross-sectional study conducted in France between June 1, 2012 and January 28, 2013, in which 968 physicians (general practitioners [GPs] and diabetologists [DBs]) recruited about 3,700 patients. Details of the study design are described elsewhere.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This was a sub-analysis of data in patients ≥75 years old from the previously published OREDIA study. 13 OREDIA was a multicenter, observational, cross-sectional study conducted in France between June 1, 2012 and January 28, 2013, in which 968 physicians (general practitioners [GPs] and diabetologists [DBs]) recruited about 3,700 patients. Details of the study design are described elsewhere.…”
Section: Methodsmentioning
confidence: 99%
“…This was assessed in the OREDIA (Observation of patients with REnal disease and DIAbetes) cross-sectional study conducted in France in 2012 to look at the therapeutic management of T2DM patients with chronic kidney disease (CKD) and to evaluate how RF was taken into account for treatment decisions. 13 …”
Section: Introductionmentioning
confidence: 99%
“…The results of this study indicated that many patients still tended to use these drugs, despite being aware of the side effects of oral drugs such as glibenclamide. Similarly, previous studies have shown that 18% to 61% of patients in stage 3 and higher stages of CKD have been treated with sulfonylureas, which has been a forbidden practice [7,8,11]. This non-compliance with the guidelines can be attributed to different reasons.…”
Section: Discussionmentioning
confidence: 93%
“…Another study was conducted in France and it was found that the general practitioners and diabetes specialists did not take into account the proposed recommendations and, thus, they prescribed metformin for 63% of patients with stage 3 of CKD and 33% of patients with stage 4 of CKD. Also, they prescribed sulfonylureas for 51% and 61% of patients with stage 3 and stage 4 of CKD, respectively [8].…”
Section: Introductionmentioning
confidence: 99%
“…Frequency of severe hypoglycaemia was 20 times higher in patients who were treated with other drugs as compared to metformin users [18]. Overall, it seems that between 25% and 33% of patients with T2D and CKD stage 3 are treated with metformin (frequently without proper dose adjustment) [21]. Some experts argue that metformin can be used in a dose of 500 mg once daily also in T2D patients with GFR 15-30 mL/min (with temporary withholding or withdrawal, when GFR is lower than 15 mL/min) [22].…”
Section: Metforminmentioning
confidence: 97%